A projection of the future effects of quantum computation on information privacy and information security - Skinner, Geoffrey; Chang, Elizabeth (Emerald Publishing, 2006)
Many of the current issues with Information Privacy have been the result of inadequate consideration for privacy during the planning, design and implementation of Information Systems and communication networks. The area of Quantum Computation is still in its infancy, and a truly functional quantum computer has not been implemented. However, it is anticipated that within the next decade it may be feasible. This presents a unique opportunity to give due consideration to Information Privacy in the realm of future quantum computational devices and environments while they are still in their infancy. This paper provides an overview of the key Information Privacy issues that we feel may arise with the evolution and realization of quantum computation. Additionally we propose an integrated approach of technical, legal and social elements to address these issues.